Hydrogel Synthesis Directed Toward Tissue Engineering: Impact of Reaction Condition on Structural Parameters and Macroscopic Properties of Xerogels - Borivoj Adnadjević; Jelena Jovanović (International Journal of Polymer Science)
The existence of correlation and functional relationships between reaction conditions (concentrations of crosslinker, monomer and initiator, and neutralization degree of monomer), primary structural parameters (crosslinking density of network, average molar mass between crosslinks, and distance between macromolecular chains), and macroscopic properties (equilibrium swelling degree and xerogel density) of the synthesized xerogels which are important for application in tissue engineering is investigated. The structurally different xerogels samples of poly(acrylic acid), poly(methacrylic acid), and poly(acrylic acid-g-gelatin) were synthesized by applying different methods of polymerization: crosslinking polymerization, crosslinking polymerization in high concentrated aqueous solution, and crosslinking graft polymerization. The values of primary structural parameters and macroscopic properties were determined for the synthesized xerogels samples. For all of the investigated methods of polymerization, an existence of empirical power function of the dependence of primary structural parameters and macroscopic properties on the reaction conditions was established. The scaling laws between primary structural parameters and macroscopic properties on average molar mass between crosslinks were established. It is shown that scaling exponent is independent from the type of monomer and other reaction conditions within the same polymerization method. The physicochemical model that could be used for xerogel synthesis with predetermined macroscopic properties was suggested.